Measuring progress in attaining targets - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
TO GUIDE, TRACK, AND LEARN FROM OUR EFFORTS TO REDUCE MALNUTRITION, WE REQUIRE CREDIBLE, TIMELY, AND USEFUL DATA ON NUTRITION OUTCOMES AND INPUTS. IN THE ERA of the Millennium Development Goals (MDGs), the amount of data available to assess progress in development grew rapidly through formal surveys, administrative data, civil registration, and mobile telephones (UN 2014b; World Bank and WHO 2014).